Fluid and thermal characteristics of flow through rectangular and elliptical curved ducts under different gravity conditions - Nadim, N.; Chandratilleke, T.; Narayanaswamy, Ramesh (2011)
Active interaction between centrifugal and buoyancy forces in curved channel has been investigated numerically in different gravity condition. Given interaction makes the flow patterns fundamentally different with straight channels; nevertheless, either of these forces domination leads to a different vortices structure and heat transfer quality. Three-dimensional, incompressible, laminar model has been used to compare rectangular and elliptical cross-sections in different gravity conditions as local and average heat transfer discussed regarding vortices structure effect. Based on the discussion different cross section has been briefly compared and concluded in term of stability whereas gravity is subjected to variation.